2013
DOI: 10.1103/physrevc.87.014307
|View full text |Cite
|
Sign up to set email alerts
|

Shape coexistence and high-Kstates in74Se populated following theβdecay of

Abstract: Excited states in74 Se were populated following the ǫ/β + decay of 74 Br, mainly from the J=K=4, 13.8 keV β-decaying isomer. Off-beam γ-ray spectroscopy was performed with the array of Clover HPGe detectors at WNSL Yale. Many new transitions were observed and rigorous spin assignments were made based on γ-γ angular correlations. The β-decay strength was found to proceed almost entirely to a few high lying states near 4500 keV, which are consistent with deformed two-quasi neutron high-K configurations. These do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
8
1
Order By: Relevance
“…It was reported that in 70 Se, the oblate shape near the ground state evolves quickly to a prolate shape at higher spins [10]. Further experiments suggested that in 72 Se, there is no well-defined shape for the lowest levels due to shape mixings [11], and the low-lying states in 74 Se show coexistence of spherical and prolate shapes [12].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was reported that in 70 Se, the oblate shape near the ground state evolves quickly to a prolate shape at higher spins [10]. Further experiments suggested that in 72 Se, there is no well-defined shape for the lowest levels due to shape mixings [11], and the low-lying states in 74 Se show coexistence of spherical and prolate shapes [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that this contradiction can be understood by the parity change across the N = 40 shell gap [3][4][5][6]. Moving to heavier isotones of N = 40 with increasing proton number, there have been many experimental evidences suggesting an increasing collectivity, for example those in the Ge [7,8] and Se isotopes [9][10][11][12]. With Z approaching 40, the N = Z isotone 80 Zr is known to be strongly deformed [13], and signs of a shell closure disappear completely and the nucleus can be regarded as a good rotor.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations